Novel insights into the Citrus sinensis nonhost response suggest photosynthesis decline, abiotic stress networks and secondary metabolism modifications - Daurelio, Lucas Damian (2015)
Plants are constantly exposed to stress factors. Biotic stress is produced by living organisms such as pathogens, whereas abiotic stress by unfavourable environmental conditions. In Citrus species, one of the most important fruit crops in the world, these stresses generate serious limitations in productivity. Through biochemical and transcriptomic assays, we had previously characterised the Citrus sinensis (L.) Osbeck nonhost response to Xanthomonas campestris pv. vesicatoria (Doidge), in contrast to Asiatic citrus canker infection caused by Xanthomonas citri subsp. citri (Hasse). A hypersensitive response (HR) including changes in the expression of several transcription factors was reported. Here, a new exhaustive analysis of the Citrus sinensis transcriptomes previously obtained was performed, allowing us to detect the over-representation of photosynthesis, abiotic stress and secondary metabolism processes during the nonhost HR. The broad downregulation of photosynthesis-related genes was correlated with an altered photosynthesis physiology. The high number of heat shock proteins and genes related to abiotic stress, including aquaporins, suggests that stresses crosstalk. Additionally, the secondary metabolism exhibited lignin and carotenoid biosynthesis modifications and expression changes in the cell rescue GSTs. In conclusion, novel features of the Citrus nonhost HR, an important part of the plants' defence against disease that has yet to be fully exploited in plant breeding programs, are presented.